Chromatographic evaluation and QSAR optimization for benzoic acid analogues against carbonic anhydrase III. (June 2015) - Alzweiri, Muhammed; Al-Balas, Qosay; Al-Hiari, Yusuf
Abstract An HPLC-size exclusion method was developed as an assay method to evaluate the binding of tested compounds with carbonic anhydrase III (CAIII) enzyme. Inhibition of CAIII by a group of benzoic acid analogues was characterized by vacancy (negative) peak intensity representing the fraction of the compounds bound with CAIII enzyme. Interestingly, p-hydroxyl benzoic acid and aspirin were found potent inhibitors against CAIII with affinity constants of 9954 and 9013 M−1 respectively. Affinity values of twenty training compounds were modeled against thirty-five descriptors derived from their structures. Strong correlation was obtained between the affinity values and the formal charge of the molecules. Docking studies on training set compounds generated consensus scores having a strong agreement with affinity factors obtained from the chromatographic analysis.